An Integrated Research Model of Olympic Podium Performance - Din, C.; Paskevich, D. (International Journal of Sports Science and Coaching, 2013)
The purpose of this article is to critically synthesize theoretical frameworks from leadership research and present a new integrated model for the study of contemporary Olympic sport leadership. The empirical work and leadership theories that this model grows out of are reviewed. This discussion builds support for the heuristic value of the integrated research model of Olympic podium performance. Although research models have been problematised by some coaching scholars, it is argued that the proposed research framework has the potential to inspire questions, challenge assumptions, and begin a leadership dialogue which foregrounds Olympic medalists' and their coaches' voices and experiences. The integrated research model is an antecedent, behavior, and consequence model. The antecedent phase is inspired by Côté et al.'s Coaching Model and includes the coach's cognitive map for sport performance. The behavior phase of this model is largely aligned with transformational leadership behaviors outlined in Chelladurai's sport in the pursuit of excellence framework and the coach-athlete relationship is included in this phase of the model. The consequence or outcome is narrowly defined as an Olympic podium performance. Future research in this unique sport leadership context and inspired by this research model is proposed.